Demographic and Clinical Factors Associated with Mechanisms of Open Globe Injury in the United States: A Multi-Center Study - Anant S; Casella A; Greenfield JA; Miller SC; Wang KY; Momenaei B; Lee K; Mansour HA; Justin GA; Makhoul KG; Bitar RA; Lorch A; et al. (Clinical Ophthalmology)
Shruti Anant,1 Alicia Casella,2 Jason A Greenfield,2 Sarah C Miller,1 Kristine Y Wang,3 Bita Momenaei,3 Karen Lee,3 Hana A Mansour,3 Grant A Justin,4 Kevin G Makhoul,5 Racquel A Bitar,5 Alice Lorch,5 Grayson W Armstrong,5 Taku Wakabayashi,3 Yoshihiro Yonekawa,3 Kara M Cavuoto,2 Fasika Woreta1 1Wilmer Eye Institute, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 2Bascom Palmer Eye Institute, University of Miami School of Medicine, Miami, FL, USA; 3Wills Eye Hospital, Thomas Jefferson University, Philadelphia, PA, USA; 4Duke Eye Center, Duke University School of Medicine, Durham, NC, USA; 5Massachusetts Eye and Ear, Harvard Medical School, Boston, MA, USACorrespondence: Shruti Anant, Wilmer Eye Institute, Johns Hopkins University School of Medicine, 1800 Orleans St, Baltimore, MD, 21287, USA, Tel +1-703-389-3753, Email sanant1@jh.eduPurpose: We sought to examine the demographic and clinical risk factors associated with specific mechanisms of open globe injuries (OGIs) and identify predictors of Zone III injuries across multiple tertiary eye care centers.Patients and methods: 1570 patients with OGIs presenting to the Wilmer Eye Institute, the Bascom Palmer Eye Institute, Massachusetts Eye and Ear, and Wills Eye Hospital between 2018– 2021 were retrospectively reviewed. Multinomial and binomial logistic regression models were used to evaluate associations between demographic and clinical risk factors with injury mechanisms and Zone III injuries.Results: Among the study population (74.2% male, mean age 48.2 years), falls (21.3%), construction work (16.2%), and assaults (10.0%) were the most common injury mechanisms. Black patients had higher risk of assault-related OGIs (relative risk ratio [RRR], 6.41; 95% confidence interval [CI], 2.06– 19.93; p< 0.001) and elderly patients > 61 years showed increased risk for falls (RRR, 10.45; 95% CI, 2.22– 49.10; p=0.003). Eyelid laceration was significantly associated with assaults (RRR, 5.58; 95% CI, 1.59– 19.65; p=0.007) and falls (RRR, 4.81; 95% CI, 1.61– 14.34; p=0.005), while iris prolapse was associated with assaults (RRR, 3.23; 95% CI, 1.12– 9.32; p=0.03) and construction work injuries (RRR, 1.99; 95% CI, 1.12– 3.52; p=0.02). Zone III injuries were independently associated with eyelid laceration (prevalence ratio [PR], 1.62; 95% CI, 1.20– 2.18; p< 0.001), relative afferent pupillary defect (RAPD) (PR, 2.42; 95% CI, 1.71– 3.43; p< 0.001), and retrobulbar hemorrhage (PR, 2.77; 95% CI, 1.76– 4.36; p< 0.001).Conclusion: This multi-institutional study identified distinct demographic risk profiles for different OGI mechanisms and clinical predictors of severe injuries. These findings suggest opportunities for targeted prevention strategies and may aid in early identification and triage of severe OGIs.Plain Language Summary: Open globe injuries (OGIs), traumatic eye injuries that pierce through the eye wall, can lead to permanent vision loss if not treated quickly. Identifying which patient populations are most at risk for OGIs, and the specific factors that increased likelihood of injury, can guide more effective prevention and treatment efforts. Our study aimed to identify the common causes of OGIs and their risk factors by analyzing patient data from four major eye hospitals in the United States.We reviewed the medical records of 1570 patients who presented to the hospital with OGIs. The most common causes of injury were falls, construction work, and assaults. Different populations faced different risks, such as: Black patients, who had a higher risk of assault-related injuries, and elderly individuals, especially women, who were more likely to be injured from falls. We found that lacerations of the eyelid were linked with assaults and falls, and iris prolapse (when the colored part of the eye is displaced) were linked to assaults and construction work injuries. Additionally, more severe injuries (Zone III injuries, which extend to the back of the eye) were associated with eyelid lacerations, changes in pupil response (relative afferent pupillary defect, or RAPD), and bleeding behind the eye (retrobulbar hemorrhage).This study provides important insights into which demographic and clinical factors put patients at risk for different mechanisms of OGIs. Our findings may be used to help identify severe cases earlier and guide targeted prevention efforts.Keywords: ocular trauma, epidemiology, demographics, etiology, prevention